Improving students' problem solving ability in solving mathematical problems on linear function topic through PBL model assisted by GeoGebra with TaRL approach - Refni Adesia Pradiarti; Anies Fuady; Lila Puspitasari (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
The aim of this research is to enhance mathematical problem-solving abilities in linear function content through the use of GeoGebra and the Teaching at the Right Level (TaRL) technique in conjunction with the Problem Based Learning (PBL) learning model. This research is a classroom action research conducted in class VIIID of SMPN 25 Malang, with 32 students as the subjects of the study. The planning, execution, observation, and reflection phases were all included in the two cycles of the study. The instruments used in this study are problem-solving ability tests and student activity observation sheets. The results show that students' problem-solving skills improved from an average of 39.25% (pre-test) to 57.25% in cycle I, and further increased to 81.77% in cycle II. The classical completeness based on the class average score also increased from 28.12% (pre-test) to 65.62% (cycle I), and then reached 81.25% (cycle II). The use of GeoGebra in the PBL model helped students understand the graph of linear functions, while the TaRL approach helped tailor the learning to the diverse needs of the students. This study proves that the combination of the PBL model and TaRL approach can effectively enhance students' mathematical problem-solving skills. This study contributes to mathematics education by demonstrating the practical integration of differentiated instruction (TaRL) and interactive technology (GeoGebra) within a PBL framework to significantly improve students’ problem-solving abilities in linear function topics.